Preference for endoscopic screening of upper gastrointestinal cancer among Chinese rural residents: a discrete choice experiment - Liu, Ruyue; Lu, Youhua; Li, Yifan; Wei, Wenjian; Sun, Chen; Zhang, Qianqian; Wang, Xin; Wang, Jialin; Zhang, Nan (Frontiers in Oncology, 2022)
Background The low uptake rate of upper gastrointestinal cancer (UGC) screening substantially reduces the benefits of endoscopic screening. This study aimed to obtain residents’ UGC screening preferences to optimize screening strategies and increase the participation rate. Methods A discrete choice experiment (DCE) was conducted to assess UGC screening preferences of 1,000 rural residents aged 40 to 70 years from three countries (Linqu, Feicheng, and Dongchangfu) of Shandong province in China. The DCE questionnaire was developed from five attributes: out-of-pocket costs, screening interval, regular follow-up for precancerous lesions, mortality reduction, and screening technique. The data from the DCE were analyzed within the framework of random utility theory using a mixed logit model. Results In total, 926 of 959 residents who responded were analyzed. The mean (SD) age was 57.32 (7.22) years. The five attributes all significantly affected residents’ preferences, and the painless endoscopy had the most important impact (β=2.927, P<0.01), followed by screening interval of every year (β = 1.184, P<0.01). Policy analyses indicated that switching the screening technique to painless endoscopy would increase the participation rate up to 89.84% (95%CI: 87.04%-92.63%). Residents aged 40–49, with a history of cancer, with a family income of more than ¥30,000 were more likely to participate in a screening. Conclusions UGC screening implementation should consider residents’ preferences to maximize the screening participation rate. Resources permitting, we can carry out the optimal screening program with shorter screening intervals, lower out-of-pocket costs, less pain, follow-up, and higher UGC mortality reduction.